2009
DOI: 10.1039/b817913a
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase ozonolysis of β-caryophyllene (C15H24). Part II: A theoretical study

Abstract: The O(3)-initiated oxidation of beta-caryophyllene, a sesquiterpene emitted in forested areas, was theoretically characterized for the first time using DFT quantum chemical calculations combined with statistical kinetic RRKM/master equation analysis and variational transition state theory. O(3)-Addition occurs primarily, >95%, on the endocyclic double bond without a barrier, leading to a total rate coefficient of 8.3 x 10(-24) T(3.05) exp(1028 K/T) cm(3) molecule(-1) s(-1), with a slight negative T-dependence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
138
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(162 citation statements)
references
References 57 publications
(95 reference statements)
22
138
1
1
Order By: Relevance
“…The calculated barrier of 72 kJ/mol agrees well with a value of 71.5 kJ/mol 25 that has been published very recently by Fang et al, 25 using a similarly high accuracy level of theory. The mHEAT value also lies within the range of 67-75 kJ/mol 6,25,40 reported earlier in the literature. It should be noted that the calculated barrier is higher than the experimental estimate of ≤67 kJ/mol.…”
Section: Reaction Mechanismsupporting
confidence: 61%
See 1 more Smart Citation
“…The calculated barrier of 72 kJ/mol agrees well with a value of 71.5 kJ/mol 25 that has been published very recently by Fang et al, 25 using a similarly high accuracy level of theory. The mHEAT value also lies within the range of 67-75 kJ/mol 6,25,40 reported earlier in the literature. It should be noted that the calculated barrier is higher than the experimental estimate of ≤67 kJ/mol.…”
Section: Reaction Mechanismsupporting
confidence: 61%
“…Syn-CH 3 CHOO could also proceed through a ring-closure step leading to methyl-dioxirane, but this pathway has a significantly higher barrier (100-110 kJ/mol 25,[38][39][40] ). Such a cyclization cannot compete with the 1,4 H-shift under atmospheric conditions and will not be considered further.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…β-caryophyllene has received particular attention, being one of the most reactive and abundant sesquiterpenes, and SOA yields have been reported in a number of ozonolysis and photo-oxidation studies (Hoffmann et al, 1997;Griffin et al, 1999;Jaoui et al, 2003;Lee et al 2006a, b;Winterhalter et al, 2009;Alfarra et al, 2012). As a result, its atmospheric degradation has been the subject of a number of experimental and theoretical mechanistic appraisals (Calogirou et al, 1997;Jaoui et al, 2003;Lee et al, 2006b;Kanawati et al, 2008;Winterhalter et al, 2009;Nguyen et al, 2009;Zhao et al, 2010;Li et al, 2011;Chan et al, 2011), and several established oxidation products have been used in tracer studies to show that β-caryophyllene-derived SOA makes potentially important contributions to ambient fine particulate matter at a number of locations Parshintsev et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The general methodology of mechanism construction was based on the rules described in detail by Jenkin et al (1997) and Saunders et al (2003), with the chemistry adjusted and augmented (in certain areas substantially) to represent information reported in a number of experimental and theoretical studies of β-caryophyllene degradation available at the time of construction (Shu and Atkinson, 1994;Calogirou et al, 1997;Atkinson and Arey, 2003;Jaoui et al, 2003;Lee et al, 2006a, b;Kanawati et al, 2008;Nguyen et al, 2009). The complete mechansim consists of 1626 reactions of 591 closed-shell and radical species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using ultraviolet photo electron spectroscopy (UPS) combined with theoretical calculation examined the ionization cross sections and first ionization energies for some sesquiterpenes, but failed to obtain the complete picture of a potentially significant part of atmospheric chemistry and environmental effects of these materials [22][23][24]. Experimental studies of ozonolysis of sesquiterpenes, which showed that semi-volatile products were produced in gas-phase reactions, were limited to individual configurations [13,21]. Currently, no laboratory measurements and simulation have been performed to explain the field-based results that sesquiterpenes exerted negative effects on climate change because of their absorption in UV region [14,17,32].…”
Section: Introductionmentioning
confidence: 99%